Autologous Stem Cell Transplantation in the Treatment of Amyloidosis – Can Manipulation of the Autograft Reduce Treatment-Related Toxicity? - Akkök, Çiğdem Akalin; Bruserud, Øystein (IntechOpen, 2011)
None